2009 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--5270
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Of Children’s Mechanistic Reasoning About Linkages And Levers In The Context Of Engineering Design

Abstract: Reasoning about mechanisms is one of the hallmarks of disciplined inquiry in science and engineering. Despite the central importance of mechanistic reasoning, its origins are not well understood. Numerous curricular efforts involve simple machines and related physical systems, but these do not yet build toward a systematic and longer-term vision for promoting the development of reasoning about mechanisms. The research we describe here was developed in partnership with a team of engineers and science educators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…(Bolger et al, 2011, p. 4) (a) Children design and build toys called MechAnimations. (b) Machines composed of levers are constructed from pegboard, links, and brads.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…(Bolger et al, 2011, p. 4) (a) Children design and build toys called MechAnimations. (b) Machines composed of levers are constructed from pegboard, links, and brads.…”
Section: Methodsmentioning
confidence: 99%
“…They note that children can be supported to reason about aspects of angle, length, orientation, form, dimension and transformation in ways that provide accessible jumping off points for the refinement of mechanistic as well as mathematical conceptions. In fact, researchers have shown that mathematical description of phenomena in science and engineering effectively supports mechanistic reasoning (Bolger et al, 2011, 2012; Weinberg, 2017a). Bolger and colleagues (2011, 2012) and Weinberg (2017a) described the relationship between mathematical description and mechanistic reasoning about link and pivot systems within engineering design.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This assessment has principally been used in studies focused on mechanistic reasoning about simple systems of levers (Weinberg, 2012(Weinberg, , 2014(Weinberg, , 2017a(Weinberg, , 2017bWeinberg & Sorensen, 2018). Thus, this assessment would also have been useful in other research focused on children's mechanistic reasoning about systems of linkages (Bolger et al, 2012;Bolger, Kobiela, Weinberg, & Lehrer, 2009;Bolger, Kobiela, Weinberg, & Lehrer, 2010;Bolger, Weinberg, Kobiela, Rouse, & Lehrer, 2011;.…”
Section: Assessment Usementioning
confidence: 99%